2010
DOI: 10.1089/acm.2009.0286
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Chromium Picolinate for Weight Loss

Abstract: Background: Chromium is an essential trace element and nutritional supplement that has garnered interest for use as a weight loss aid. Objective: This trial assesses the effects of chromium picolinate supplementation, alone and combined with nutritional education, on weight loss in apparently healthy overweight adults. Design: This was a randomized, double-blind, placebo-controlled trial of 80 otherwise healthy, overweight adults assessed at baseline for central adiposity measured by computerized tomography. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 43 publications
1
29
0
5
Order By: Relevance
“…Our results are congruent with findings from a recent study performed in our laboratory showing no effect of 1000 mcg of chromium picolinate on weight loss and adiposity in 80 overweight individuals (26). Other recent trials have found similar results.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are congruent with findings from a recent study performed in our laboratory showing no effect of 1000 mcg of chromium picolinate on weight loss and adiposity in 80 overweight individuals (26). Other recent trials have found similar results.…”
Section: Discussionsupporting
confidence: 93%
“…Many of these included subjects with impaired glucose tolerance and/or dyslipidaemia. In most studies, chromium intake from the diet was not assessed and information on total chromium intake is therefore not available (Riales and Albrink, 1981;Anderson et al, 1983b;Offenbacher et al, 1985;Anderson et al, 1987;Press et al, 1990;Hermann et al, 1994;Boyd et al, 1998;Hermann et al, 1998;Cefalu et al, 1999;Joseph et al, 1999;Amato et al, 2000;Bahijri, 2000;Volpe et al, 2001;Gunton et al, 2005;Anton et al, 2008;Krikorian et al, 2010;Yazaki et al, 2010;Kim et al, 2011;Masharani et al, 2012). The Panel considers that no conclusions can be drawn from these supplementation studies, performed mainly in subjects with impaired glucose tolerance and/or dyslipidaemia, with regard to an effect of total dietary chromium intake on glucose and/or lipid metabolism in healthy populations.…”
Section: Criteria On Which To Base Dietary Reference Valuesmentioning
confidence: 99%
“…[28] Food cravings [29-32] and negative affect [33, 34] have been identified as instrumental triggers for binge eating, and high disinhibition is common among individuals who binge eat [35, 36] and is associated with poor treatment outcome. [37] On the other hand, other studies have failed to find any effect of chromium supplementation on glucose metabolism or body weight [38, 39]. Across studies, the treatment protocol has varied, and the optimal dosage level and treatment duration for efficacy remain unknown.…”
Section: Introductionmentioning
confidence: 99%